Between Legalism and Mystical Intuism: Sunan Kalijaga’s Qibla Direction in Pati and Demak Grand Mosque - Nurkhanif, Muhammad; Raharjo, Raharjo; Musyafak, Najahan (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2023)
This study aims to discover the process of determining the direction of the qibla by Sunan Kalijaga (one of Walisongo), employing a mystical and intuition (divine inspiration) method. This study is a qualitative field research using a socio-cultural approach. The research objects are the Baiturrahim Gambiran Pati Mosque and Demak Grand Mosque, Central Java. These mosques were built by Sunan Kalijaga. The results of this study revealed why the people of Gambiran Pati and Demak Grand Mosque still use the Sunan Kaljaga version of the qibla direction compared to the qibla direction using scientific technology. Some factors that influence include, first, the historical value factor of the Baiturrahim Mosque and Demak Grand Mosque as the guardian mosque and also the legendary figure of Sunan Kalijaga. Second, The socio-cultural characteristics of the Gambiran Pati and Demak communities are familiar with the mystical Kejawen.Contribution: This research contributes to understanding the method of determining the direction of the qibla by Sunan Kalijaga using mystical and intuitive approaches. It focuses on two historical mosques, the Baiturrahim Mosque in Gambiran Pati and the Grand Mosque of Demak, considering their historical, religious, and socio-cultural factors.